Polycaprolactone/chlorophyllin sodium copper salt nanofibrous mats prepared by electrospinning for soft tissue engineering - Muhammad Zikri Aiman Zulkifli; Nur Hidayatul Nazirah Kamarudin; Darman Nordin (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study examined the process of synthesising biodegradable nanofibres made up of polycaprolactone (PCL) and chlorophyllin sodium copper (CSC) through electrospinning for scaffolding in tissue engineering. Scaffolds provide a platform for cell regeneration for repairing damaged human tissues or organs. However, the issue lies in developing scaffolding that will provide a favourable environment for cell attachment and proliferation. One way to address this concern is to add CSC, which has been widely used in biomaterial applications, to the nanofibres. The structure and morphology of the nanofibres in this research were determined by using a scanning electron microscope (SEM), and their chemical properties were tested by using Fourier-transform infrared spectroscopy (FTIR). Moreover, the diameter and adhesive force of the nanofibres were investigated by using an atomic force microscope (AFM). The SEM examination revealed that the PCL/CSC nanofibres lost their fibrous structure, and the FTIR results proved that the nanofibres synthesised by electrospinning still consisted of PCL and CSC. The AFM examination showed that the diameter and adhesive force of PCL/CSC nanofibres were less than those of PCL nanofibres. This outcome resulted from the CSC’s inability to generate fibres on its own. Furthermore, its noncrystalloid structure prevented it from providing inner enhancement for PCL nanofibres. Hence, further studies are needed to ensure that PCL/CSC nanofibres can be used as an innovative type of scaffolding to provide an appropriate environment for living cells.